THE TOEFL LISTENING STRATEGIES EXPERIENCED BY NURSING STUDENTS OF POLTEKES BANTEN - imtihan hanim (Universitas Muhammadiyah Tangerang, 2023)
AbstractThis study was executed to identify the strategies that students encountered when taking the TOEFL, particularly in the listening section. The descriptive qualitative technique was used in the study. It used the interview as a data collecting instrument. The research subjects were the seventh grade of Nursing students in POLTEKES Banten. The following strategies were used to examine the data: data collecting, data display, data reduction, and conclusion drafting. This study included 25 seventh semester students of Nursing Study Program who were chosen using random sample approaches. According to the findings of this study, it indicated the strategies of their listening test were concentrating, comprehend the listening instruction, having a good time management, predicting the questions, focusing on keywords and assigned in supportive environment.